2009
DOI: 10.1016/j.jhep.2009.01.021
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ agonist attenuates alcohol-induced hepatic insulin resistance and improves liver injury and repair

Abstract: Background/Aims Chronic ethanol exposure impairs liver regeneration due to inhibition of insulin signaling and oxidative injury. PPAR agonists function as insulin sensitizers and anti-inflammatory agents. We investigated whether treatment with a PPARδ agonist could restore hepatic insulin sensitivity, survival signaling, and regenerative responses vis-a-vis chronic ethanol feeding. Methods Adult rats were fed isocaloric liquid diets containing 0% or 37% ethanol, and administered a PPARδ agonist by i.p. injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
126
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 48 publications
6
126
0
Order By: Relevance
“…Variation in the expression of these enzymes influences the sensitivity and the adaption to ethanol consumption (13). PPAR␤/␦ can protect against chemically induced liver injury through multiple mechanisms including inhibition of steatosis, inhibition of NF-kB-dependent signaling, and inhibition of inflammation (10,11,16,17). A previous study revealed that exposure to carbon tetrachloride (CCl 4 ) caused an increase in hepatic Cyp2b10 expression, and this induction was mediated by PPAR␤/␦, which was not due to differences in the relative expression of CAR (10), similar to the results observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in the expression of these enzymes influences the sensitivity and the adaption to ethanol consumption (13). PPAR␤/␦ can protect against chemically induced liver injury through multiple mechanisms including inhibition of steatosis, inhibition of NF-kB-dependent signaling, and inhibition of inflammation (10,11,16,17). A previous study revealed that exposure to carbon tetrachloride (CCl 4 ) caused an increase in hepatic Cyp2b10 expression, and this induction was mediated by PPAR␤/␦, which was not due to differences in the relative expression of CAR (10), similar to the results observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that PPAR␤/␦ protects against alcoholic liver disease by inhibiting steatosis, amino acid metabolism, and pyridoxal phosphate activity (8). Similarly, ligand activation of PPAR␤/␦ restores insulin sensitivity and also protects against ethanolinduced liver injury (17 (28). Further studies are needed to delineate the specific activities of PPAR␤/␦ in Kupffer cells and hepatocytes that underlie these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The inhibition of Akt phosphorylation leads to impaired liver regeneration. 30 We thus determined the phosphorylation of Akt in the liver. The phosphorylation of Akt (Ser473), which results in its activation, was markedly induced within 6 and 12 hours after PH in normal mice.…”
Section: Inhibition Of Akt Phosphorylation Is Associated With Elevatementioning
confidence: 99%
“…6,7 On the other hand, several nuclear receptors, PPARa, PPARg, PPARd, RAR, and HNF4a, have been shown to be involved in alcohol-induced liver injury. [8][9][10][11][12] Considering the importance of CAR in P450 enzyme expression and metabolisms of glucose and lipids, we ask whether CAR has a role in modulating alcoholinduced liver injury. In this study, we compared both chronic and acute alcohol-induced liver injury in CAR À/À and wildtype mice.…”
mentioning
confidence: 99%